(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The composites based on aluminum alloys obtained by friction stir processing (FSP) combine the advantages of lightweight aluminum composites with the well-refined structure obtained by deformation in plastic state. When reinforcing elements in the form of powders or nanoplates are introduced in the process, of mixing they are evenly distributed in the processes zone, which acquires a fine-grained structure. The study examines specific results in the use of various tools and materials, as well as some basic parameters of the process in terms of surface smoothness, defects and some performance characteristics of the tested samples, such as strength, ductility, hardness and corrosion resistance.